Breast Implant–Associated Anaplastic Large Cell Lymphoma (BIA-ALCL): Are You Covered?. (15th April 2021) - Ha, Michael; Ngaage, Ledibabari M; Zhu, Kevin; Hricz, Nicholas; Slezak, Sheri; Rasko, Yvonne M
Abstract: Background: Breast implant–associated anaplastic large cell lymphoma (BIA-ALCL) is a locally aggressive T-cell lymphoma that can develop following breast implantation. In 2017, and updated in 2019, the National Comprehensive Cancer Network (NCCN) recommended total capsulectomy with implant removal as definitive therapy. Objectives: The aim of this study was to evaluate the US insurance coverage for the management of BIA-ALCL and compare it to the NCCN recommendations. Methods: A cross-sectional analysis of US insurance policies for coverage of BIA-ALCL treatment was conducted. Insurance companies were selected based on their market share and state enrollment. Medical necessity criteria were abstracted from the publicly available policies. Results: Of the 101 companies assessed, only 30 (30%) had a policy for the management of BIA-ALCL. Of those policies, all (n = 30, 100%) provided coverage of the implant removal of the breast diagnosed with BIA-ALCL. For the contralateral breast implant, 20 policies (67%) covered their removal, but significantly fewer did so if the implant was placed for cosmetic reasons vs medically necessary (n = 13 vs n = 20, 43% vs 67%; P = 0.0026). Twenty-one policies (70%) covered an implant reinsertion, but fewer would do so if the implant was cosmetic rather than medically necessary (n = 5, 17% vs 70%; P < 0.0001). Conclusions: There was notable intercompany variation in the coverage of BIA-ALCL treatment, some of which is unnecessarily based on whether the original reason for the breast implant was cosmetic or medically necessary. This variability may significantly reduce access to definitive treatment in patients with a BIA-ALCL diagnosis.